PRODUCTIVE AND SPATIAL NEXUSES OF RECENT REAL ESTATE DYNAMICS: A STUDY ON HIGH AND MEDIUM STANDARD RESIDENTIAL PRODUCTION IN PELOTAS (RS) - Soares Sa Britto, Natalia Daniela [UNESP]; Sobarzo, Oscar (Univ Federal Fluminense, 2020)
The article presents an investigation about the new medium and high standard residential products produced in the city of Pelotas (RS), between 2009 and 2016, with the objective of identifying the main capitals and agents, their logic and production and valorization strategies, as well as considering the implications of these productive nexuses in the structuring of the urban space. From the point of view of the analysis of business logic, are highlighted: the recent strategies of production, commercialization and financing of medium and high standard residential products, which go from national scale advertising initiatives, such as the use of strategies of the starchitecture type, to the agency of private and venture capital investments, which allow greater investments' profitability, liquidity and security, signaling for a greater diversification of the surplus appropriated by the capitals that integrate the real estate circuit locally. In relation to the resulting socio-spatial processes, are highlighted: the constitution of a diffuse and marked by territorial discontinuities urban fabric, as well as the propagation of new forms of business intervention and management of space based on New Urbanism ideas. Both processes tend to be carried out as part of the strategies to recreate real estate offer, reinforcing dynamics that increase socio-spatial differentiations and inequalities.
Keywords: real estate production; agents; closed residential spaces; new urbanism; Pelotas